Incretin Hormones: A Versatile Bio-Chemical for Biological Activities - Pandey, Shivanand (International Journal of Pharmaceutical & Biological Archive, 2010)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0; @font-face font-family:AdvPSMEL; panose-1:0 0 0 0 0 0 0 0 0 0; mso-font-alt:"MS Mincho"; mso-font-charset:128; mso-generic-font-family:auto; mso-font-format:other; mso-font-pitch:auto; mso-font-signature:0 134676480 16 0 131073 0; @font-face font-family:"\@AdvPSMEL"; panose-1:0 0 0 0 0 0 0 0 0 0; mso-font-charset:128; mso-generic-font-family:auto; mso-font-format:other; mso-font-pitch:auto; mso-font-signature:0 134676480 16 0 131073 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0in; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman"; .MsoChpDefault mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt; @page Section1 size:8.5in 11.0in; margin:1.0in 1.0in 1.0in 1.0in; mso-header-margin:.5in; mso-footer-margin:.5in; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> The stimulation of intracellular pathways through GLP- 1R and GIPR can have either synergistic or opposing modes of action. GLP-1 has multiple actions on a number of tissues and on the endocrine pancreas, but its principal action is potentiation of glucose-induced insulin secretion. Without diabetes, although the predominant effect is the lowering of blood glucose. However, the incretin effect is greatly reduced or even lost inpatients with type 2 diabetes a result that has also been seen in other metabolic disorders such as obesity and insulin resistance. The incretin effect further implies a reduced insulin response to ingested carbohydrates and, subsequently, increased blood glucose levels. What remains unclear is why the incretin effect is reduced in type 2 diabetes. Is it the secretion of incretin hormones themselves or is the action of incretin hormones attenuated. Human studies have shown that the GLP-1 response is certainly reduced in patients with type 2 diabetes vs. subjects with normal glucose metabolism.